Rivista Italiana di Sociologica, announced (Quarterly Journal of Economics, 1897)
Journal Article Rivista Italiana di Sociologica, announced Get access The Quarterly Journal of Economics, Volume 11, Issue 4, July 1897, Page 450, https://doi.org/10.1093/qje/11.4.450 Published: 01 July 1897